Using Remap-STAD Learning Assisted by The GitMind Application to Improve Students' Problem-Solving Skills in Biology Education (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Several studies have highlighted the essential nature of students' problem-solving skills. However, these studies have also revealed that students' problem-solving skills in Indonesia are currently lacking. Consequently, there is a need to empower and improve these skills. This research aims to investigate the impact of implementing the Remap-STAD learning model, with the assistance of the GitMind application, in order to enhance students' problem-solving abilities in the field of biology. The research design employed in this study is a pretest-posttest non-equivalent control group design. The research sample comprises 70 students from class X MIPA at SMAN 9 Malang, East Java. The experimental group was taught using the Remap-STAD learning model, supplemented with the GitMind application, while the control group was taught using the STAD learning model alone. Problem-solving skills were assessed through a description test comprising eight questions. Greenstein's (2012) scoring rubric, which encompasses eight indicators including problem identification, application of problem-solving steps, identification and evaluation of solutions, defense of solutions, real-world applications, inductive reasoning, and deductive reasoning, was employed for scoring. ANCOVA was utilized to analyze the data on problem-solving skills, with a significance level set at 5%. The Kolmogorov-Smirnov test was conducted to assess the normality of the data, while Levene's Test of Equality of Variances was used to evaluate homogeneity. The data analysis findings indicate significant treatment effects for the learning model (p < 0.05), thereby accepting the research hypothesis. The results demonstrate that the Remap-STAD learning model, combined with the GitMind application, can notably enhance students' problem-solving skills in the context of biology education. Consequently, the implementation of Remap-STAD, with assistance from the GitMind application, necessitates the development of instructional tools tailored to the chosen learning model and the specific skills being measured. This approach will promote and enhance learning activities, particularly in improving students' problem-solving capabilities.